How classical and entrepreneurial brand management increases the performance of internationalising SMEs? - Kusi, Samuel Yaw; Gabrielsson, Peter; Baumgarth, Carsten (Elsevier, 2022)
Research is limited on how accumulated international experience and decision-making style propel internationalising SMEs toward brand orientation. Our study builds a model of the process on classical and entrepreneurial brand management principles plus the firm's applied experience and decision-making logics. An online survey of 235 internationalising SMEs found that adopted decision-making logic mediated the relationship between cumulative international experience and international brand orientation. We conclude that managers and planners must select the most appropriate approach to international brand management permitted by available international firm-specific experience if they are to achieve strong international brand orientation and superior financial performance.
Keywords: International entrepreneurial experience; International marketing planning experience; Effectuation; International brand orientation; Internationalising SMEs; Financial performance; fi=Kansainvälinen liiketoiminta|en=International Business|